AB0178 Menopause Is A Predictor for The Development of Anti-Citrullinated Protein Antibodies in Women at Risk for Rheumatoid Arthritis. (15th July 2016) - Alpizar-Rodriguez, D.; Müller, R.; Möller, B.; Dudler, J.; Ciurea, A.; Von Mühlenen, I.; Kyburz, D.; Zufferey, P.; Bas, S.; Gascon, D.; Lamacchia, C.; Roux-Lombard, P.; et al.
Abstract : Background: Many controversies exist about the role of sex hormones and reproductive factors in the development of rheumatoid arthritis (RA). Post-menopause is a period of important hormonal and immunologic changes and has been associated with increased risk of seronegative-RA (1). Earlier age at menopause has been associated with increased risk of RA (2), therefore factors related to menopause may be relevant for the development of preclinical phases of RA. Objectives: To study the association between reproductive and menopausal factors and the risk of development systemic autoimmunity associated with RA, in particular of anti-citrullinated protein antibodies (ACPA), in women at increased risk for RA. Methods: This is a nested cohort study within an ongoing prospective study of individuals genetically at risk of developing RA, namely first degree relatives of patients with RA (FDRs). Individuals without clinical evidence of RA were enrolled, and followed-up yearly with clinical and laboratory assessments. We included all women with available ACPA status (anti-CCP 2, 3.1 or 3.0). Reproductive and menopausal factors were self-reported. We operationally defined perimenopausal women as those with recent menopause (<3 years) or aged between 47 to 53 years with menopause-related symptoms. Total ovulatory years were estimated by substracting the age at menarche from the age at menopause minus one year for every childbirth and the total years of oral contraceptive use as previously described (3). We used logistic regression to analyze univariable and multivariable associations between ACPA-positivity and menopause factors. Results: Of the 809 FDR women analyzed, 50 (6%) were ACPA-positive and had a median age of 46 (interquartile range (IQR): 34–56) years. Characteristics of FDR women are shown in Table 1 . In univariable analysis, older age, ≥1 tender joint on examination, post-menopausal status and total ovulatory years were significantly associated with ACPA positivity. Perimenopausal status tended to be associated with ACPA status (OR:1.8, 95%CI:0.9–3.4), but did not reach significance. Other menopausal factors, such as age at menopause, earlier menopause or surgical menopause were not associated with ACPA positivity. Due to high correlation between age and menopausal status (r=0.73), we included tobacco smoking, post-menopausal status and having ≥1 tender joint on examination in the multivariable adjusted analyses, post-menopausal status and ≥1 tender joint on examination remained independently associated with ACPA positivity. Conclusions: Post-menopausal FDR women have an increased risk of ACPA positivity, suggesting menopausal hormonal changes are associated with the development of ACPAs, which may be linked to previously described increase of pro-inflammatory cytokines during menopause (4). References: Bengtsson C, et al. Arthritis Rheumatol 2014;66:S1261. Beydoun HA, et al. Menopause 2013;20:930–5. Costenbader KH, et al 2007; 56(4):1251–62. Kim OY, et al. Age 2012;34:415–2. Disclosure of Interest: None declared